As rendeiras de morros da Mariana: projetos de design - Poeta, Joana Áurea Medeiros Lima (2014)
This dissertation analyzes the actions of three projects. They include design, handcraft, and culture valorization executed between the years 2000 and 2010 in the community of the "bilro" by the lacemakers of "Morro da Mariana", in the state of Piauí. The research methodology applied in loco focused on the lacemakers' interview which searched for their perceptions and feelings about their handcraft and the insertion of design in their day to day activities through their work projects. The lacemakers' interviews guided the investigation in this study about the possible swap of information among the designers and artisans involved. Through the discussion of their actions, intentions and consequences about projects realized at Morro da Mariana, this research proposes questioning how the design projects may or may not contribute to the handcraft community, based on the needs of each place.